Prevalence of Obesity and Its Impact on Outcome in Patients With COVID-19: A Systematic Review and Meta-Analysis - Helvaci, Nafiye; Eyupoglu, Nesrin Damla; Karabulut, Erdem; Yildiz, Bulent Okan (Frontiers in Endocrinology, 2021)
Background and Objective: Obesity has been reported as a risk factor for adverse outcomes in COVID-19. However, available studies presenting data on obesity prevalence in patients with COVID-19 have conflicting results. The objective of this systematic review and meta-analysis is to evaluate the prevalence of obesity in these patients and to stratify the estimates by illness severity. Methods: We performed a literature search with the use of Medline/PubMed and Google Scholar database from December 1, 2019 to June 27, 2020 and systematically reviewed studies reporting the number of obese patients with real-time reverse transcriptase polymerase chain reaction (rRT-PCR)-confirmed SARS-CoV-2 infection. Results: Nineteen studies were identified. The pooled obesity prevalence rates were 0.32 (95% CI: 0.24-0.41) in hospitalized patients, 0.41 (95% CI: 0.36-0.45) in patients admitted to intensive care unit, 0.43 (95% CI: 0.36-0.41) in patients needing invasive mechanic ventilation (IMV), and 0.33 (95% CI: 0.26-0.41) in those who died. Obesity was associated with a higher risk for hospitalization [Odds ratio (OR):1.3, 95% CI: 1.00-1.69; I2 52%, p=0.08], ICU admission (OR:1.51, 95% CI: 1.16-1.97; I2 72%, p<0.01), and IMV requirement (OR:1.77, 95% CI: 1.34-2.35; I2 0%, p=0.64). The increase in risk of death did not reach statistical significance (OR:1.28, 95% CI: 0.76-2.16, p=0.35) which might be due to obesity survival paradox and/or unidentified factors. Conclusions: Our data indicate that obese subjects may be at higher risk for serious illness if infected and obesity may play a role in the progression of COVID-19.